Optimal investment and equilibrium pricing under ambiguity - Anthropelos, Michail; Schneider, Paul (Review of Finance, 2024)
Abstract We study a model for portfolio selection under uncertainty along with market equilibria that are associated with the optimal positions. Allowing for both ambiguity-seeking and ambiguity-averse market participants, model-implied demand functions resemble observed bid–ask spreads, and are consistent with extant limited-participation results based on more specialized ambiguity settings. A Pareto-efficient second-best equilibrium arises from constraining the portfolio allocations of ambiguity seekers. It implies that heterogeneity in ambiguity preferences is sufficient for mutually beneficial transactions even among all else homogeneous traders. Our results reconcile many observed phenomena in liquid high-information financial markets, such as portfolio inertia and negative risk premia.